Polymer Chain Reaction (PCR): Principle and Applications - Noorhan Khalid Shafeeq (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2021)
The new, standard molecular biologic system for duplicating DNA enzymatically devoid of employing a living organism, like E. coli or yeast, represents polymerases chain reaction (PCR). This technology allows an exponential intensification of a minor quantity of DNA molecule several times. Analysis can be straightforward with more DNA available.